IMPLEMENTATION OF MEDAN MAYOR REGULATION NUMBER 58 OF 2023 CONCERNING ENFORCEMENT OF DISCIPLINE AND CODE OF ETHICS FOR STATE CIVIL APPARATUS EMPLOYEES OF MEDAN CITY GOVERNMENT - Razanah Azzahra Zulfa Nasution; Subhilhar; Heri Kusmanto (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Based on data from the Medan City Government, there are many employees in the Medan City Government environment throughout 2023 - 2024 since the enactment of the Medan Mayor's Regulation Number 58 of 2023, who violate the enforcement of discipline and the code of ethics, in addition there are still many State Civil Apparatus who come to work but are not in accordance with the effective working hours that have been determined. This study aims to analyze the Implementer in implementing the Medan City Mayor's Regulation No. 58 of 2023 in order to enforce the discipline of Medan City Government ASN and what factors hinder the Implementer in enforcing ASN discipline in the Medan City Government environment. The research method used in this study is the qualitative research method. Qualitative research is a procedure in research that can produce descriptive data in the form of words or spoken from the behavior of people to be observed, for example behavior, perceptions, motivations, actions and others. Data is collected through primary data and secondary data, primary data is obtained through in-depth interviews with informants and conducting observations, while secondary data is obtained through articles and journals obtained via the internet. The results of the study show that (1) Implementers in the field (including agency leaders and BKPSDM) strive to convey disciplinary policies consistently, on time, and clearly through daily briefings, weekly evaluation meetings, and the use of digital media. This is in line with George Edwards III's theory which emphasizes the importance of transmission, consistency, and clarity in policy communication. The importance of quality Human Resources (HR) in developing ASN capacity and competence through training and workshops plays a major role in improving discipline. Trained and motivated HR will better understand and internalize disciplinary values, so that the implementation of disciplinary policies can run more optimally. Adequate Budget Support in allocating budgets in the HR sector supports the provision of supporting infrastructure such as personnel information systems and digital attendance tools as well as funding training and competency development programs. (2) The inhibiting factor for ASN discipline in Medan City is ineffective communication in implementing information regarding disciplinary policies which are often not conveyed consistently and clearly to all ASN. This results in different interpretations between work units, so that the implementation of disciplinary rules is not evenly distributed. The lack of commitment and assertiveness from unit leaders in enforcing disciplinary rules is one of the main obstacles. Inconsistent internal oversight and lack of follow-up on violations have led to continued indisciplinary behavior.